PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN POWTOON PADA MATA PELAJARAN IPA DI SD - Hendriani, Maifit; Permata Dewi, Indah (LP2M Universitas Adzkia, 2023)
This research is motivated by the lack of interest of students in learning, because the media used is not yet concrete, the textbook used for science lessons on Water Cycle material has only one picture and no explanation, educators use the lecture method, the media used by educators is only can be seen by students without being able to try it themselves. This study aims to determine the validity, practicality and effectiveness of Pop Up Book learning media in science subjects for fifth grade elementary school.This type of research is R&D using a 4-D model (define, design, development, and dissemination). At the dissemination stage, a trial was conducted on 10 fifth grade elementary school students. The data collection instrument in this study was in the form of a validation sheet (for material experts, linguists, and media experts). Practical instruments are in the form of a questionnaire for educators and students and the effectiveness as seen from the learning outcomes of students.The results showed that the Pop Up Book media in the Water Cycle Science subject in class V with a material expert validation score of 92.5% with a very valid category, linguistic expert validation with a score of 95.8% with a very valid category and media expert validation with a score of 95.8% with a very valid category, and the average overall value of the validation with a score of 94.7% (Very Valid). For practicality results from 1 educator, the average score is 86,8% with very practical criteria, while for practicality the ten students get an average value of 85%with practical criteria. For the results of the effectiveness of getting an average value of 96.7% in learning 1 with very effective criteria, in learning 2 getting an average value of 97.3%. So it can be concluded that the development of Pop Up Book learning media in science subjects for fifth grade elementary school is very valid, practical, and effective